Sikh Religion and Contentions around Caste - Surinder S. Jodhka (Religions, 2024)
Caste has been a contentious subject in Sikhism. While the Sikh theological canons have vehemently opposed its practice, it continues to be present among the Sikhs, including its discriminatory culture. The obvious response of the Sikh leaders and scholars has been to ask for ‘a moral self-criticism’. The issue thus becomes praxeological, a matter of aligning ‘practice with the theory’. This is a simplistic response. Such a narrative also does not allow us to raise relevant questions about the contemporary framings of caste as a hegemonic construct. It also does not permit us to engage with its diverse empirics among the Sikhs and its other contextual dynamics. The paper argues that to move forward, we need to critically explore the currently popular notions of caste, most of which are drawn from orientalist and colonial constructs. They present India as being a land of Hindus and the practice of caste being its essential feature. The Indian nationalists enthusiastically endorsed such a framing because they found it useful for making claims about India’s cultural unity. Drawing from a large volume of historical and empirical writings, the paper identifies problems with such a narrative of caste which sees it as a purely religious practice. It further argues for a need to look at the materiality of caste. Religious prescripts, such as Manusriti, function as ‘ideological signals’ that promote and legitimize it. In contrast, the ideological signals provided by the Gurus and the Sikh religious canons are unambiguously opposed to such ascription-based hierarchies.